Acellularized Uvea Hydrogel as Novel Injectable Platform for Cell‐Based Delivering Treatment of Retinal Degeneration and Optimizing Retinal Organoids Inducible System. Issue 23 (17th October 2022) - Li, Guilan; Liu, Sheng; Chen, Wenfei; Jiang, Zhijian; Luo, Yuanting; Wang, Dongliang; Zheng, Yingfeng; Liu, Yizhi
Abstract: Replenishing the retina with retinal pigment epithelial (RPE) cells derived from pluripotent stem cells (PSCs) has great promise for treating retinal degenerative diseases, but it is limited by poor cell survival and integration in vivo. Herein, porcine acellular sclera and uvea extracellular matrix (ECM) and their counterpart hydrogels are developed, and their effects on the biological behavior of human induced pluripotent stem cell (hiPSC)‐derived RPE cells (hiPSC‐RPE) and embryoid body (hiPSC‐EB) differentiation are investigated. Both acellular ECM hydrogels have excellent biocompatibility and suitable biodegradability without evoking an obvious immune response. Most importantly, the decellularized uvea hydrogel‐delivered cells' injection remarkably promotes the hiPSC‐RPE cells' survival and integration in the subretinal space, rescues the photoreceptor cells' death and retinal gliosis, and restores vision in rats with retinal degeneration for a long duration. In addition, medium supplementation with decellularized uvea peptides promotes hiPSC‐EBs onset morphogenesis and neural/retinal differentiation, forming layered retinal organoids. This study demonstrates that ECM hydrogel‐delivered hiPSC‐RPE cells' injection may be a useful approach for treating retinal degeneration disease, combined with an optimized retinal seeding cells' induction program, which has potential for clinical application. Abstract : The decellularized uvea hydrogel delivered cells' injection, promotes human induced pluripotent stem cell (hiPSC) derived retinal pigment epithelial cells' survival and integration in the subretinal space remarkably, and restores vision in degenerative retina for a long duration. In addition, medium supplementation with decellularized uvea peptides promotes hiPSC derived embryoid bodies' onset morphogenesis and neural/retinal differentiation, forming layered retinal organoids.